Analisis Penerapan Teori Akuntansi Positif Terhadap Kasus Derivatif Pada PT. Mayora Indah VS Bankers Trust Internasional PLC, CS - Jihan Mawaddah; Sintya Kirana; Nafisah Nuqma Nasyiwa (Jurnal Riset Akuntansi, 2024)
This research aims to examine the application of positive accounting theory to the derivatives case involving PT. Mayora Indah vs Bankers Trust International PLC, CS. The methodology utilized in this study is descriptive analysis employing a qualitative approach. The data used here is secondary data, sourced from research journals that have been reprocessed. The research findings indicate that the derivatives transaction conducted by PT. Mayora Indah does not qualify as hedging aligning with the principles of prudential banking. This determination is due to the fact that the master agreement for said transaction is also fictitious, thus lacking validity in the derivative transaction.